Influence of drying temperature and pretreatment on the drying characteristics and quality of dried cashew (Anacardium occidentale L.) apple slices - Olalusi, Ayoola Patrick (Array, 2019)
This study evaluated the mineral content, browning extent, proximate content, the sensory analysis in the yellow variety of cashew apple slices, for both fresh and after being subjected to pretreatment, at three different drying temperatures. Fresh cashews were harvested, sliced into 7 mm thickness, pretreated by dipping the slices into ascorbic acid and dried at the temperature of 45 °C, 55 °C and 65 °C using the hot air convective dryer at a constant air velocity of 0.8 m/s. During the drying the weight loss was measured initially at an interval of every 30 minutes for the first five hours and later at an hour hour interval. The analysis of minerals content (magnesium and calcium) and proximate analysis which included pH, color, vitamin C content, and tannin content was carried out. In addition, sensory evaluation for taste, texture, aroma, appearance and overall acceptability was carried out according to the 9-point hedonic scale using raw cashew apple as a control. For each of the plots for the drying curves from the mechanical drying test, they are mostly in the failing rate period. The results showed that the moisture loss from the cashew slices increased with increase in drying temperature and time of drying. It was observed that drying temperature has an influence on the proximate content, browning extent and mineral content of the cashew slices. An increase in temperature leads to high losses of vitamin C, less browning effect and high losses of tannin. The result of the sensory evaluation revealed that the pretreated sample dried at a temperature of 55 °C was the most acceptable.